Pengaruh Project Based Collaborative Learning terhadap Hasil Belajar Bahasa Indonesia dalam Materi Teks Prosedur Siswa Kelas V - Heryon Bernard Mbuik; Netti Nertelda Henuk; Roswita Lioba Nahak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examined the effect of Project-Based Collaborative Learning (PBCL) on improving Indonesian language learning outcomes, particularly in procedural text material, among fifth-grade students at SDK Don Bosco 4 Kupang. Using a quantitative approach and a one-group pretest–posttest design, the research involved 11 students as participants. Data were collected through learning outcome tests administered before and after the implementation of PBCL. The results showed a significant improvement in students’ post-test scores compared to pre-test scores, indicating that PBCL effectively enhanced comprehension and the ability to write procedural texts. The findings confirm that PBCL promotes active engagement, cooperation, and meaningful learning experiences for elementary students. Therefore, PBCL can be recommended as an alternative instructional model for Indonesian language learning in elementary schools.